2018
DOI: 10.1016/j.jtcvs.2017.09.162
|View full text |Cite
|
Sign up to set email alerts
|

Lung adenocarcinoma with intraoperatively diagnosed pleural seeding: Is main tumor resection beneficial for prognosis?

Abstract: Our study demonstrated improved progression-free and overall survival after main tumor and visible pleural nodule resection in patients with lung adenocarcinoma with intraoperatively diagnosed pleural seeding. Further randomized trials are needed to define the role of main tumor resection in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 33 publications
5
47
2
Order By: Relevance
“…In the last decade, several singlecenter retrospective studies with sample sizes ranging from 25 to 110 patients have shown favorable outcomes for M1a patients undergoing PTR, with MSTs ranging from 15 to 64 months and three-year OSs ranging from 34.2% to 82.9%, respectively. 6,12,[17][18][19][20][21][22] A recent meta-analysis of nine retrospective studies 23 also suggested that PTR was a beneficial prognostic factor among cM0 and pM1a NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, several singlecenter retrospective studies with sample sizes ranging from 25 to 110 patients have shown favorable outcomes for M1a patients undergoing PTR, with MSTs ranging from 15 to 64 months and three-year OSs ranging from 34.2% to 82.9%, respectively. 6,12,[17][18][19][20][21][22] A recent meta-analysis of nine retrospective studies 23 also suggested that PTR was a beneficial prognostic factor among cM0 and pM1a NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Yun et al 6 reported a similar rate (approximately 50%) of EGFR mutation and EGFR-TKI treatment between a resection and an exploration group in patients with localized pleural seeding first detected during surgery. In the most recent study by Li et al 12 approximately 67% of patients with adenocarcinomas (n = 29) received EGFR-TKI therapy, which contributed, in part, to the surprising surgical outcomes of patients with lung adenocarcinoma with intraoperatively diagnosed pleural seeding. However, the question remains whether main tumor resection still needs to be performed among EGFR mutation-positive patients who could have excellent survival receiving only EGFR-TKI therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 , 2 ] Although every pleural dissemination is classified as the same stage, M1a, pleural dissemination is not a single entity of disease but a spectrum of disease with various tumor burden encompassing from limited pleural seeding to overt malignant pleural effusion (MPE). [ 3 , 4 ] Dry pleural dissemination (DPD) is a relatively early stage of pleural dissemination defined as pleural seeding without effusion and can be detected radiologically or surgically in a patient with clinically resectable lung cancer. DPD is detected in 1.2% to 2% of clinically resectable lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, on the basis of our recent experience with cytoreductive surgery and hyperthermic intrathoracic chemotherapy (HITHOC) for mesothelioma and malignant pleural effusion [2,3], and some recent publications reporting good survival in selected patients with stage IVA lung cancer [4][5][6], we strongly believe that not all patients with stage IVA (M1a) NSCLC are the same and that longer survival can be obtained in those with disease confined in the hemithorax, and therefore a "new" form of precision (individualised) surgery should be explored as part of a multidisciplinary treatment modality. ZHOU et al [7] performed a meta-analysis on the effect of debulking surgery and HITHOC on malignant pleural effusion for various primary cancers.…”
Section: Introductionmentioning
confidence: 99%